Does size and buoyancy affect the long-distance transport of floating debris?. (18th August 2015) - Ryan, Peter G
Abstract: Floating persistent debris, primarily made from plastic, disperses long distances from source areas and accumulates in oceanic gyres. However, biofouling can increase the density of debris items to the point where they sink. Buoyancy is related to item volume, whereas fouling is related to surface area, so small items (which have high surface area to volume ratios) should start to sink sooner than large items. Empirical observations off South Africa support this prediction: moving offshore from coastal source areas there is an increase in the size of floating debris, an increase in the proportion of highly buoyant items (e.g. sealed bottles, floats and foamed plastics), and a decrease in the proportion of thin items such as plastic bags and flexible packaging which have high surface area to volume ratios. Size-specific sedimentation rates may be one reason for the apparent paucity of small plastic items floating in the world's oceans.